The impact of sacrospinous ligament fixation on pre-existing nocturia and co-existing pelvic floor dysfunction symptoms - Wenk, Maren; Rakhimbayeva, Aidana; Sutherland, Suzette E.; Roovers, Jan-Paul; Yassouridis, Alexander; Liedl, Bernhard (International urogynecology journal, 2020)
To evaluate whether nocturia and coexisting pelvic floor symptoms in women with pelvic organ prolapse (POP) can be improved by ligamentous fixation of apical vaginal prolapse to the sacrospinous ligament.